Interdisciplinarity in academic training in health care and the importance of teamwork (International Seven Journal of Multidisciplinary, 2023)
Interdisciplinarity is a way of structuring and organizing a greater amount of comprehensive knowledge, facilitating the understanding of multiple causes that affect a given reality. The objective is to know the importance of interdisciplinarity in academic training for teamwork. This is a bibliographical, descriptive, qualitative research. Using the descriptors Interdisciplinary Health Team, Professional Training and Health Professionals, 321 articles were found in the VHL data portal, with 4 final articles being selected. Thus, it is understood that interdisciplinarity in academic training has proven to be a great tool for learning other professionals, presenting its benefits for continuous assistance, in the short and long term, for the team and its users. It is concluded that it takes articulation between the team, dialogue, cooperation between teamwork and this is only possible through interdisciplinarity, when it is developed in the academic environment.